Assessing the Recording of Adequate Care Plans in Child and Adolescent Mental Health Services: A Clinical Audit - Sabrina Choudary; Hana Yokoyama-King; Annabel Ariyathurai; Kiruthika Sivasubramanian (BJPsych Open, 2025)
Aims: Care plans can be integral to community psychiatric services to evidence personalised care through shared decision-making. Black Country Healthcare NHS Foundation Trust (BCHFT) guidelines require a documented care plan for each patient, outlining their needs, goals and preferences. Additionally, the GMC advises doctors to keep contemporaneous records for children and young people. This maintains clarity with the patient, their family, GP, and the wider multidisciplinary team.